Using leaf color charts to estimate leaf nitrogen status of rice - Yang, Woon-Ho; Peng, Shaobing; Huang, Jianliang; Sanico, Arnel L.; Buresh, Roland J.; Witt, Christian (Wiley, 2003)
Leaf color charts (LCCs) have substituted for chlorophyll meter (SPAD) to estimate leaf N status of rice (Oryza sativaL.) and to properly time N fertilizer application. The objectives of this study were to (i) compare three different types of LCC in estimating leaf N status, (ii) determine if specific leaf weight (SLW) affects the estimation of dry weight–based N concentration (Ndw) by LCC, and (iii) determine the relationship between LCC scores and SPAD values. Two field experiments were conducted in the Philippines with different N rates and cultivars grown during 2000 wet season and 2001 dry season. The LCC score and SPAD reading were taken on uppermost fully expanded leaves at three growth stages, and SLW was calculated as the ratio of dry weight to leaf area. Nitrogen content was determined by micro‐Kjeldahl procedure and expressed as Ndwand leaf area–based N content (Na). There was a linear relationship between LCC scores and Ndwat each growth stage (R2range of 0.25–0.97) and across growth stages (R2range of 0.46–0.62). Adjusting LCC scores for SLW (LCC/SLW) greatly improved the prediction of Ndwacross growth stages (R2range of 0.84–0.92), suggesting that leaf thickness affects LCC scores. Leaf color chart estimated Nabetter than Ndwacross growth stages. Leaf color chart scores were closely related to SPAD values (R2range of 0.62–0.98). Strong correlations existed among the scores of the three types of LCC (rrange of 0.93–0.99). They are all suitable for use by rice farmers in timing N topdressing.